The Advances in Phospholipids-Based Phase Separation Gels for the Sustained Release of Peptides, Proteins, and Chemotherapeutics - Jianxia Dong; Xueru Zhou; Qing Li; Ruohui Zheng; Jing Chen; Yuzhe Liu; Xin Tong; Zhuoya Wan; Tao Gong (MDPI AG, 2024)
Implantable drug delivery systems formed upon injection offer a host of advantages, including localized drug administration, sustained release, minimized side effects, and enhanced patient compliance. Among the various techniques utilized for the development of in situ forming drug implants, solvent-induced phase inversion emerges as a particularly promising approach. However, synthetic polymer-based implants have been associated with undesirable effects arising from polymer degradation. In response to this challenge, a novel category of drug delivery systems, known as phospholipids-based phase separation gels (PPSGs), has emerged. These gels, characterized by their low initial viscosity, exhibit injectability and undergo rapid transformation into in situ implants when exposed to an aqueous environment. A typical PPSG formulation comprises biodegradable components, such as phospholipids, pharmaceutical oil, and a minimal amount of ethanol. The minimized organic solvents in the composition show good biocompatibility. And the relatively simple composition holds promise for industrial-scale manufacturing. This comprehensive review provides an overview of the principles and advancements in PPSG systems, with specific emphasis on their suitability as drug delivery systems for a wide range of active pharmaceutical ingredients (APIs), spanning from small molecules to peptides and proteins. Additionally, we explore the critical parameters and underlying principles governing the formulation of PPSG-based drug delivery strategies, offering valuable insights on optimization strategies.